Morphology study on different composition of bentonite and silica sand in green sand mould for zinc alloy - Zatil Alyani, Mohd Amin; Faizul, Che Pa; Mohd Ichwan, Nasution, Prof. Madya Ir. (Universiti Malaysia Perlis, 2010)
International Conference on X-Rays and Related Techniques in Research and Industry (ICXRI 2010) jointly organized by Universiti Malaysia Perlis (UniMAP) and X-Ray Application Malaysia Society (XAPP), 9th - 10th June 2010 at Aseania Resort Langkawi, Malaysia.